Controllable synthesis of nitrogen-doped hollow carbon nanospheres with dopamine as precursor for CO2 capture. Issue 94 (26th September 2016) - Xia, Kechan; Yu, Yifeng; Li, Yunqian; Li, Shuhui; Wang, Yuying; Wang, Guoxu; Zhang, Hongliang; Chen, Aibing
Abstract : Nitrogen-doped hollow carbon nanospheres are synthesized by using dopamine as carbon and nitrogen sources and tetraethyl orthosilicate as structure-assistant agent. Abstract : Nitrogen-doped hollow carbon nanospheres (N-HCSs) have been synthesized by self-polymerization of dopamine on silica spheres using the modified Stöber method. The fabrication process uses dopamine as carbon and nitrogen source and tetraethyl orthosilicate as a structure-assisting agent. The particle sizes and shell thicknesses of the N-HCSs can be easily tuned in the range of 270–700 nm and 30–55 nm, respectively, by simply modifying the ethanol/water volume ratios. The surface areas of N-HCSs are in the range of 345–463 m 2 g −1, and the total pore volumes are in the range of 0.34–0.52 cm 3 g −1 . The obtained N-HCSs have uniform mesoporous size of ∼4.0 nm, and high nitrogen loading content of 7.2 at%. Besides, the N-HCSs exhibit a considerable performance for CO2 capture with a capacity of 3.09 mmol g −1 at 25 °C and 1.0 bar and a good cycling stability.